Understanding the Knight in the Age of the Crusades, c.1100-1204 - Beaman, Jack (2021)
Medieval military terminology in crusading sources from c.1100-1204 is the focus of this study. An interrogation of when knights developed into a coherent grouping is central to the thesis. Definitions of knights on a military, economic and social basis are explored. The approach exposes and emphasises often overlooked nuances of medieval military structure.